2023
DOI: 10.3390/cancers15020492
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Role of Cancer Stem Cell Marker ALDH1A3 in Cancer and Beyond

Abstract: Aldehyde dehydrogenase 1A3 (ALDH1A3) is one of 19 ALDH enzymes expressed in humans, and it is critical in the production of hormone receptor ligand retinoic acid (RA). We review the role of ALDH1A3 in normal physiology, its identification as a cancer stem cell marker, and its modes of action in cancer and other diseases. ALDH1A3 is often over-expressed in cancer and promotes tumor growth, metastasis, and chemoresistance by altering gene expression, cell signaling pathways, and glycometabolism. The increased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…It is well appreciated that ALDH1A3 is an important driver of stemness in multiple cancer types, including breast, melanoma, glioblastoma, prostate, non-small cell lung cancer (NSCLC), head and neck cancer, and colon cancer [47]. Indeed, ALDH1A3 has been shown to enhance metastasis, clonogenicity, and chemoresistance [48,49].…”
Section: Aldh1a3mentioning
confidence: 99%
“…It is well appreciated that ALDH1A3 is an important driver of stemness in multiple cancer types, including breast, melanoma, glioblastoma, prostate, non-small cell lung cancer (NSCLC), head and neck cancer, and colon cancer [47]. Indeed, ALDH1A3 has been shown to enhance metastasis, clonogenicity, and chemoresistance [48,49].…”
Section: Aldh1a3mentioning
confidence: 99%
“…Aldehyde dehydrogenase 1 family, member A3 (ALDH1A3) is one of 19 ALDH isoforms that convert aldehydes to carboxylates. ALDH1A3 is overexpressed in various cancers and is a marker of cancer stem cells, which contributes to cancer initiation, metastasis, therapeutic resistance, and relapse ( 15–17 ). ALDH1A3 mediates diverse intracellular events, such as retinoic acid biosynthesis and mitochondrial metabolism ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the three isoforms, ALDH1A3 has been described to be overexpressed in different neoplasms, including pancreatic cancer, high-grade gliomas, and ovarian cancer, but is not expressed in the non-neoplastic cells. Specifically, ALDH1A3 is highly expressed in drug resistant cancer stem cells (CSCs), characterized by the capability to promote self-renewal, clonogenic growth and metastases [ 16 , 17 ]. Recently, an analysis of 84 MPM patients from the TGCA database revealed that high ALDH1A3 expression is significantly associated with worse prognosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%